(untitled) (Margalla Papers, 2025)
This article examines the threat of violent extremism and terrorism in South Asia and Africa, comparing counter-violent extremism (CVE) strategies to identify effective measures for sustainable security. It explores the sociopolitical, economic, and cultural factors driving radicalisation and terrorist activities in both regions. South Asian countries like Pakistan, Afghanistan, and India face extremism fuelled by historical grievances, political instability, and religious ideologies. In Africa, nations such as Nigeria, Somalia, and Kenya contend with groups like Boko Haram and Al-Shabaab, exacerbated by poverty, governance issues, and ethnic conflicts. The study aims to highlight successful interventions and the limitations of existing approaches, emphasizing the role of international organizations and regional bodies in shaping CVE efforts. By fostering collaboration between South Asia and Africa, the research seeks to develop comprehensive strategies to address the root causes of violent extremism and promote long-term peace and stability. Bibliography Entry Minko, Abraham Ename. 2025. "Comparative Analysis of Counter-Violent Extremism Strategies in South Asia and Africa: Lessons and Pathways for Sustainable Security." Margalla Papers 29 (1): 55-79.